New Rights for forest-based communities?: understanding processes of forest tenure reform - Larson, A.M.; Barry, D.M.; Dahal, G.R. (2010)
This article reports on findings from a research project, in more than 30 sites in 10 countries in Africa, Asia and Latin America, aimed at analyzing cases where changes in formal tenure rights for forest-based communities had recently occurred or were in process. Though by far largest proportion of the world’s forests are owned by the state, over a quarter of forests in developing countries are now owned by or assigned to communities. This suggests, at least in some ways, a marked departure from the historic trend towards centralizing. The project, led by the Center for International Forestry Research in coordination with the Rights and Resources Initiative in 2006-2008, sought to identify issues and concerns from the perspective of socially and economically vulnerable groups that were seeking rights reforms. The objectives were to understand reform processes, particularly the extent to which community rights had improved in practice. This article reports on the analysis of three aspects of the reforms: the broad global trends shaping them, challenges in implementation and outcomes for livelihoods and forests.